Pengaruh Upah dan Insentif terhadap Kepuasan Kerja pada UD. Barokah Desa Paokmotong - Yohana Safitri; Luluk Fadliyanti; Vici Handalusia Husni (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study aims to analyze the effect of wages and incentives on employee job satisfaction at UD. Barokah Desa Paokmotong. The research method used a quantitative approach with an associative type of research. The research sample included all employees of UD. Barokah, totaling 35 respondents. Primary data were obtained through questionnaires using a Likert scale and analyzed with ordinal logistic regression tests using Stata. The results of the study indicate that wages and incentives have a positive and significant effect on job satisfaction both simultaneously and partially. The research model is deemed feasible with a LR Chi-square value of 44.88 and a p-value of 0.0000, as well as a McFadden R2 value of 0.5039, indicating that variations in job satisfaction can be explained by these two compensation variables. This study emphasizes that financial compensation is a dominant factor in improving job satisfaction in small businesses such as UD. Barokah in Paokmotong Village.